Estimation Of Tenascin-X, Sphingosine and HOMA-IR Cut-Off Values For Obese Adults - Nagham Qasim Kadhim (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Tenascins are glycoproteins groups found in the extra-cellular matrix . The sphingolipidome in blood distinguished as a hundreds types of fats with many different essential chemical and physical properties. Insulin resistance is impaired biologic response of many target tissues to stimulation of insulin, and all tissues that have insulin receptors exposed insulin resistant. Materials and methods: Sixty sampling were participated, their ages ranged from (30-38) years. Biochemical measurements: insulin by AFIAS-10 , TN-X and sphingosine measured by kits by Sun Long Biotech – China. Results:- the level of Tenascin-X, sphingosine and HOMA-IR in the obese group increase significantly (P<0.01) when compared to non-obese group. Cut-off for Tenascin-X was 10.382pg./ml, for sphingosine was 10.93 ng./ml, and for HOMA-IR was 1.43 ng./ml. Conclusions: tenascin-X sphingosine and HOMA-IR were related with obesity. Tenascin-X, Sphingosine and HOMA-IR were related to obesity